2014
DOI: 10.1016/j.envint.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Repeated measurements of per- and polyfluoroalkyl substances (PFASs) from 1979 to 2007 in males from Northern Norway: Assessing time trends, compound correlations and relations to age/birth cohort

Abstract: Background Longitudinal biomonitoring studies can provide unique information on how human concentrations change over time, but have so far not been conducted for per-and polyfluoroalkyl substances (PFASs) in a background exposed population. Objectives Determine: i) serum PFAS time trends on an individual level; ii) relative compositions and correlations between different PFASs; and iii) assess selected PFAS concentrations with respect to periodic (calendar year), age and birth cohort (APC) effects. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
66
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 54 publications
14
66
3
1
Order By: Relevance
“…For fetuses and infants, two exposure pathways of PFAAs, including maternal-fetal transmission and breast feeding transmission, have attracted intensive attention in recent years (So et al, 2006b;Tao et al, 2008;Liu et al, 2010;Glynn et al, 2012;Zhang et al, 2013a,d;Nøst et al, 2014). For fetuses, significant positive correlations have been found between concentrations of PFAAs in paired samples of maternal whole blood and placenta, and between placenta and cord blood (Zhang et al, 2013a) (Fig.…”
Section: Exposure Pathway and Risk Assessmentmentioning
confidence: 98%
“…For fetuses and infants, two exposure pathways of PFAAs, including maternal-fetal transmission and breast feeding transmission, have attracted intensive attention in recent years (So et al, 2006b;Tao et al, 2008;Liu et al, 2010;Glynn et al, 2012;Zhang et al, 2013a,d;Nøst et al, 2014). For fetuses, significant positive correlations have been found between concentrations of PFAAs in paired samples of maternal whole blood and placenta, and between placenta and cord blood (Zhang et al, 2013a) (Fig.…”
Section: Exposure Pathway and Risk Assessmentmentioning
confidence: 98%
“…6), Gebbink et al [85] reported rapid declines (1.8-3.5 year disappearance half-lives) for four PFOS-precursors (MeFOSAA, EtFOSAA, FOSAA, FOSA) in the same period, between 1996 and 2012. Declining trends of the PFOS-precursor, FOSA, is furthermore demonstrated by analysis of two datasets on male serum from Norway, both of which showed an inverted U-shape temporal trend for FOSA [92,115]. For Norwegian men (40-50 year) [92], a significant increase of FOSA between 1977 and 1985 (change-point) was followed by a statistically significant decline to 2006, with later concentrations being non-detectable.…”
Section: Pfos Precursorsmentioning
confidence: 99%
“…6). No significant temporal trends for PFOS were observed in only 6 datasets of human samples [89,102,115,121,143], and two datasets of dietary items [99,142], but in each case the power to detect a trend was low. Overall, the declining trends for PFOS generally coincide with the timing of the 3M Co. phase out by 2002.…”
Section: Pfos Change Point Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nøst et al (2014) studied the temporal trends for exposure to PFAAs from 1979 to 2007 in males from Northern Norway. In five repeated measurements of PFAAs in human serum, they found that PFOA and PFOS concentrations peaked during 1994-2001 and 2001, respectively.…”
Section: Human Biomonitoringmentioning
confidence: 99%